Managing the dynamics of networks and services 5th International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2011, Nancy, France, June 13-17, 2011. Proceedings - Chrisment, Isabelle; Couch, Alva; Badonnel, Remi; Waldburger, Martin (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Autonomous Infrastructure, Management and Security, AIMS 2011, held in Nancy, France, in June 2011. The 11 revised full papers presented together 11 papers of the AIMS PhD workshps were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on security management, autonomic network and service management (PhD workshop), policy management, P2P and aggregation schemes, and monitoring and security (PhD workshop).